Gold as an effective diversifier for global equities: evidence from developed and emerging markets - Ernst, Luca Severin (2020)
Finding financial assets with a low or even negative correlation to equities has become notoriously difficult in the face of global co-integration and the financialization of commodity markets. Gold remains to be one of the assets in which investors around the world place their trust as a stabilizing force in times of adverse markets, and it is often referred to as a safe haven in the financial media. The present thesis examines gold’s diversification potential for a broad cross-section of developed and emerging markets from the perspective of both foreign and domestic investors. The empirical analysis is based on two models; (i) a linear regression model with different regressors to capture extreme market conditions, and (ii) a GARCH-DCC(1,1) model to analyze the dynamic time-varying correlations. Both approaches provide compelling evidence and support previous research that the safe haven potential of gold increases as stock returns deteriorate, i.e. when diversification is most needed. In addition, the paper finds that gold displays safe haven benefits for numerous markets with increasing global uncertainty. But with peaking volatility, financial contagion seems to predominate, and gold is no longer an effective measure to protect investors’ wealth in most markets. As regards emerging economies, the findings align with previous studies indicating that gold’s diversification potential is very limited for foreign investors. For domestic investors, in turn, gold proves to be a potential hedge and/ or safe haven asset for numerous emerging markets.